Images and words with a background story. A few critical remarks about the Polish translation of the graphic novel "Kinderland" - Katarzyna Barbara Tymoszuk (Rozprawy Społeczne)
This article presents the results of a critical translational analysis of the translation of the German graphic novel “Kinderland” by Grzegorz Janusz into Polish. The necessary background for analytical considerations is provided by: a brief outline of the reception of the comic, its most important features from a perspective of a translator, the characteristics of graphic novel as one of the types of comic book narrative, which is represented by “Kinderland”. Later in the article, translation problems will be presented, both in the visual and linguistic layers of selected fragments of the comic. Also, the translation solutions used by the Polish translator will become the subject of the author’s critical considerations.